Religious Diplomacy Promoting Peace, Collaboration, & Economic Stability - Jamil, Shafia; Atta, Misbah; Kalbi, Hanna-e- (Al-Amīr Research Journal for Islamic Studies, 2023)
This project explores the influence of religious diplomacy on economic and international relations, focusing on three key areas: identifying common interests among different religions, particularly women's rights, analyzing the role of soft power in religious diplomacy, and exploring the broader implications of religious diplomacy in international relations. The study acknowledges religion as a powerful force and aims to use it to foster cooperation and address global challenges. The first aspect focuses on identifying common interests among different religions, particularly women's rights and empowerment, to promote interfaith dialogue and collaboration. The second aspect explores the role of soft power in religious diplomacy, examining how religious leaders and institutions can use persuasion, attraction, and cultural exchange to bridge divides, promote dialogue, and enhance social cohesion, ultimately contributing to economic development. The third aspect explores the broader implications of religious diplomacy in international relations, considering both positive contributions like conflict resolution and peace building and potential risks associated with manipulating religious tensions or favoring specific religious groups. The project adopts a multidisciplinary approach, using qualitative research methods like interviews and document analysis. Key words: Religious diplomacy, Inter-faith dialogue, Soft power, International relations.